Formação docente para alfabetização e letramento: uma análise a partir do currículo oficial do curso de pedagogia da UFPA/Castanhal - SANTOS, Luana Ketellen Rêgo da Silva (2019)
Knowing how to literate a child from the initial grades of elementary school is one of the competences to be built by the students of the pedagogy course, since it is this course the responsibility for the education professional who will teach in the first years of basic education. In this sense, the work contemplates discussions about the initial formation of teachers within the scope of the pedagogy course, analyzing specifically the formation for literacy and literacy in the initial grades. The study was based on the qualitative research paradigm, being operationalized through a documentary research, taking into account also the personal experience as a graduate of Pedagogy at UFPA / Castanhal. The source of data collection consisted of official documents that guide the formation of teachers and discuss literacy in the initial grades, among them the Pedagogical Political Project of the Pedagogy Course of the Federal University of Pará / Campus de Castanhal, which was analyzed from the perspective of content analysis from the conceptions of Bardin (2006), which highlights this tool from three (3) steps: 1) Preanalysis, which corresponds to the initial phase, is the first contact with the material to be studied. It is the survey and selection of materials to be used to understand the object of study. 2) Exploitation of the material, which is the moment in which the material information will be synthesized, separating them into schemas for understanding. 3) Treatment of results, in which the results of the research, initially raw, will be observed, transforming them into data that make sense, in the light of the thoughts of scholars who discuss this subject. The discussions of the object of study were based on the contributions of Cagliari (1982, 1998, 2009), Ferreiro (1999), Kleiman (1995), Nóvoa (1995), Soares (2003, 2005, 2008), among others. From this, it is considered that the course of Pedagogy of the UFPA / Castanhal has offered the graduates an adequate training, regarding the teacher training focused on literacy and literacy in the initial grades of elementary school, in accordance with the principles and official requirements. It was also verified that the curriculum of the course covers the main objectives proposed for the development of the graduating to practice the teaching in the initial grades, discussing theories and practices related to the object of study in focus